Impact evaluation at IFPRI - Islam, Yassir; Wanmali, Sudhir; He, Jane J.; Broca, Sumiter Singh; Ahmed, Akhter (International Food Policy Research Institute, 1996)
The purpose of this note is to promote a discussion at IFPRI on impact evaluation. It discusses the benefits and problems of impact evaluation, presents several different concepts for evaluating impact, and then applies these to the five stages of IFPRI's project cycle in developing countries. It concludes with a discussion of 'next steps' which IFPRI can take in order to begin evaluating the impact of its activities and outputs.